Komodifikasi Agama dalam Bisnis Social Crowdfunding di Indonesia - Al Jawi, Amin; Nurhayati, Nurhayati; Soemitra, Andri (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2023)
This study aims to criticize and reconstruct the concept of commodification of religion in order to further reveal whether social crowdfunding business activities which are currently booming in Indonesia have become part of the practice of commodification of religion. This research is a qualitative research with a case study approach based on literature studies which is analyzed using data processing techniques Miles & Huberman with three stages, namely: data reduction, data display, conclusion and verifying. The results of the study found that: First, the practice of commodification of religion in social crowdfunding business activities and/or all other business activities must be viewed comprehensively (textually and contextually) from various perspectives so that mal-perceptions do not occur, because the commodification of religion is between marketing strategies, exploitation religion, and the need for religion which has positive and negative impacts according to their characteristics, in addition to the fact that discourse on religion has complexity and is multi-dimensional. Second, social crowdfunding business activities in Indonesia meet the criteria for the practice of commodification of religion, but are casuistic in nature, and do not apply generally to all fundraisers and/or managers of social crowdfunding platforms. The findings in this study are expected to place the concept of commodification of religion in business marketing as a whole, that the commodification of religion is not only a matter of religious exploitation and has a negative connotation. In order not to get caught up in religious exploitation practices, social crowdfunding businesses and all other business people must change their orientation, that business in religion (Islam) is not only about personal gain, but also about the benefit of society and the environment.